A Set of Roman Belt Fittings. A Beneficiarius Legati Legionis III Cyrenaicae? - Raviv, Dvir (MEGA Publishing House, 2021)
In this paper we present bronze objects from the third century CE, including military belt fittings and a plate that adorned a box or coffin. The provenance of the objects is unknown. The importance of publishing them stems from the rare mention of the name of a Roman legion, the juxtaposition of facts relevant to their dating with the geographical context, and the paucity of similar known exemplars. Having analyzed the data, we can cautiously suggest that the objects come from a tomb in northern Transjordan or southern Syria that belonged to a soldier – perhaps a beneficiarius – in the Legio III Cyrenaica stationed in the province of Arabia during the Late Roman period.